Ethnography on Trial: Introduction to the Dialogue - Yanow, Dvora (Politics, groups & identities, 2021)
In Interrogating Ethnography: Why Evidence Matters (2018), law professor and lawyer Steven Lubet mounts a concerted attack on ethnography for relying upon evidence that would not meet the standards that obtain in legal proceedings. What is ethnography, and why should this concern political scientists?